THE ROLE OF E-GOVERNMENT IN ENHANCING E-DEMOCRACY IN SELANGOR LOCAL GOVERNMENTS: AN EVALUATIVE STUDY - Nazreena binti Mohammed Yasin (Journal of Islamic, Social, Economics and Development, 2022)
Electronic government (e-Government) is a research field that studies the use of information and communication technology (ICT) in the public sector. E-Government aims to promote people's participation by using the services provided by the government and utilising modern technology to increase democratic engagement. This study uses Marianne Kneuer's framework to examine the impact of e-government on democracy in Selangor. Since there is little literature that addresses the local government website in Selangor and its relationship to the concept of e-democracy, it is critical to demonstrate the role of e-government in promoting e-democracy. Selangor local government websites can promote e-democracy by exploring three categories: free and equal access, e-participation, and e-governance. The results show that all four local government websites perform differently based on the proposed categories and the survey conducted. They make different progress and have taken many initiatives to promote edemocracy on their websites. This paper examines the contents of the websites of the selected local governments in Selangor and how they relate to e-democracy. The result shows that the websites of different states perform differently. The results collected discuss challenges to the effectiveness and efficiency of e-government and e-democracy at the local government level based on the results collected and interviews conducted with the website administrators.